Estrategias de comunicación para el cambio social en el fortalecimiento de la Organización Mujeres Valientes - Bastidas Pérez, Carlos Miguel (2015)
Communication Strategies for Social Change on strengthening the organization Mujeres Valientes is a proposal born from a specific need for the organization, to make themselves visible and position nationally. This work is divided into three chapters. In the first one, a route of the main communication theories arising in and from Latin America and propitiated by the Latin American School of Communication (ELACOM) is approached: communication for development, participatory and popular communication and finally communication for social change, which is the theory from which the communication strategies for the organization will be built. The second chapter is an approach on the organizational communication; several elements of the organizational communication are analyzed there. All of them from the perspective of social and grassroots organizations. The third chapter is an explanation of the process carried out to build communication strategies through participatory workshops with members from Mujeres Valientes; as well as the different techniques and methodologies used in these workshops. Finally the strategies proposed, as well as the communicative products are presented and conclusions and recommendations of the process are made. This proposal has not only academic relevance but also has a social relevance; benefiting an organization of women deprived of their freedom, single mothers and poor who have decided to organize for themselves to demand respect for their rights.